Teacher Performance Management in the Integrated Islamic Elementary School Qur'an Kisaran - Abdul Latif Hutagaol; Candra Wijaya; Neliwati Neliwati (EDUTEC : Journal of Education And Technology, 2023)
This study focuses on teacher performance management in integrated Islamic elementary schools Qur'an Kisaran, in this study a qualitative case study type method was used. data collection techniques using observation, interviews, and documentation. The research results show that first, in teacher performance planning, the school and teachers work together to set clear and measurable goals. Teachers also make specific performance indicators and develop detailed and structured lesson plans. In addition, professional development efforts must also be carried out by teachers to improve the quality of teaching, and they also make a performance evaluation plan. Furthermore, in implementing performance, the teacher carries out learning activities according to the curriculum, conveys subject matter in a way that is easily understood by students, measures student progress objectively, creates a classroom environment that is conducive to learning, and attends training and professional development regularly. Finally, in performance appraisal, the principal makes direct observations of each teacher with scheduled class supervision, teachers are assessed on the basis of academic progress and student achievement in the subjects taught, assessments of other teacher colleagues or fellow staff provide input on the assessed teacher's performance, and teachers compile portfolios containing evidence of their performance. In addition, teachers are also asked to do personal reflection about their performance.